Bioactive and self-healing smart materials in pulp therapy - Abdulwahab, Maha Ali; Makeynah, Hussain Abdulwahab Al; Alruwaili, Mohammed Farhan; Alhattab, Ahmed Yousef; Khulaif, Mohammed Mousa Al; Alamri, Abdulrahman Saad; Qarni, Yazeed Saeed Al; Alhabardi, Afnan Ahmad; Alreshidi, Mohammad Fudhi; Albeladi, Aseel Hamdan; Alwadai, Adel Hussain (International Journal Of Community Medicine And Public Health, 2025)
The efficiency of pulp therapy has been greatly impacted by the development of materials used in endodontic and restorative dentistry. Biologically based regenerative pulp treatment has entered a new era, specifically with the advent of smart materials, which are characterized by their capacity to react actively to environmental stimuli. Along with sealing and protecting the pulp, these materials’ bioactivity and, in certain situations, self-healing properties enable them to aid in tissue repair, lower inflammation, and promote the regeneration of the dentin-pulp complex. Calcium silicate-based sealers, Mineral Trioxide Aggregate (MTA), and bioactive materials like biodentine encourage biomineralization and the formation of reparative dentin, while self-healing systems like microcapsule-based composites can independently restore structural integrity after microcracks. The third frontier in smart dental materials is represented by stimuli-responsive formulations, which release therapeutic agents under controlled conditions in response to variations in pH, moisture content, or bacterial activity. Through an analysis of their mechanisms of action, clinical results, advancements in material science, and potential applications, this review seeks to investigate the role of bioactive and self-healing smart materials in pulp therapy. To educate researchers and clinicians about the new technologies that are changing pulp preservation and regeneration techniques in minimally invasive dentistry, the objective is to present an up-to-date summary of available data.